Institutional development and stock price synchronicity: Evidence from China - Iftekhar Hasan; Liang Song; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
Better developed legal and political institutions result in greater availability of reliable firm-specific information. When stock prices reflect more firm-specific information there will be less stock price synchronicity. This paper traces the experience of China, an economy undergoing dramatic institutional change in the last 20 years with rich variation in experiences across provinces. We show that stock price synchronicity is lower when there is institutional development in terms of property rights protection and rule of law. Further-more, we investigate the influence of political pluralism on synchronicity. A more pluralistic regime reduces uncertainty and opaqueness regarding government interventions and therefore increases the value of firm-specific information that reduces synchronicity.
URN:NBN:fi:bof-201408072083
Keywords: G14; G15; G24; G38; 330; Institutions; China; stock price synchronicity